Prognostic significance of bone marrow 2-[18F]-fluoro-2-deoxy-d-glucose uptake in diffuse large B-cell lymphoma: relation to iliac crest biopsy results. Issue 7 (July 2021) - Lim, C.H.; Hyun, S.H.; Cho, Y.S.; Choi, J.Y.; Lee, K.-H.
Abstract : AIM: To investigate the prognostic significance of bone marrow (BM) 2-[ 18 F]-fluoro-2-deoxy-d- glucose (FDG) uptake in relation to posterior iliac crest BM biopsy (BMB) results in diffuse large B-cell lymphoma (DLBCL). MATERIALS AND METHODS: Pretreatment integrated positron-emission tomography(PET)/computed tomography (CT) images of 512 DLBCL patients who underwent BMB and received rituximab combined with cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) chemotherapy were analysed retrospectively. BM uptake was assessed visually and by maximum standard uptake value (SUVmax). Associations with lymphoma-specific survival (LSS) were assessed using Kaplan–Meier and Cox regression analyses. RESULTS: FDG(+) BM was observed in 64 cases (41 focal, 12 heterogeneous, 11 diffuse). This finding distinguished iliac crest involvement (positive in 59 and negative in 453) with 89.6% accuracy (459/512) and 93.6% specificity (424/453). In BMB(+) patients, BM-to-liver SUVmax ratio >1.8 concurred perfectly with FDG(+) BM. During 52 months of follow-up, there were 156 lymphoma-related deaths. In the entire population, multivariate analysis revealed high International Prognostic Index (IPI; p< 0.001), old age ( p= 0.003), bulky disease ( p= 0.011), BMB(+) ( p= 0.028), and FDG(+) BM ( p= 0.019) as independent predictors of worse LSS. In the BMB(+) subgroup, high National Comprehensive Cancer Network-revised IPI (NCCN-IPI; p= 0.029) and FDG(+) BM ( p= 0.008) were significant independent predictors. Among BMB(+) patients with low to low–intermediate NCCN-IPI, FDG(+) BM was associated with significantly worse 2-year LSS (33.3% versus 100%; p= 0.017). The same was true among those with high–intermediate NCCN-IPI (34.7% versus 76.9%.; p= 0.026). CONCLUSION: Increased BM FDG in DLBCL is a predictor of worse LSS independent of BMB results and other prognostic variables including IPI/NCCN-IPI. Highlights: In DLBCL, increased BM FDG uptake is a predictor of worse OS independent of BMB results. In positive BMB results, BM FDG uptake and NCCN-IPI scores were useful for selecting high risk group. In DLBCL, BM FDG uptake patterns did not have an effect on predicting prognosis.